Analisis Peran Guru Kelas sebagai Fasilitator dalam Membentuk Karakter Akhlak untuk Para Siswa di MI Wahid Hasyim - Balqis, Alifah; Arifin, Badrul (LP3M Universitas Al-Qolam Malang, 2024)
This research analyzes the role of class teachers as facilitators in shaping the moral character of students at Madrasah Ibtidaiyah Wahid Hasyim. The main goal of education is to help students achieve their maximum potential through the development of inner strength, self-control, intelligence, and noble morals. Teachers play an important role as learning agents who inspire and motivate students to develop faith, spirituality and religious values. The research results show that the role of teachers as facilitators is very significant in shaping students' moral character through various religious activities, such as congregational dhuha prayers and tahfidzul Qur'an programs. Teachers also act as role models who provide examples of positive and disciplined behavior to students. In addition, emotional support and positive interactions between teachers and students help create a learning environment that is conducive to the development of student morality. Collaboration between family and school also plays an important role in shaping students' moral character. Key words: teacher; character; Islamic education; ethics